Indices of Biodiversity Pattern Based on Presence-Absence Matrices: A GIS Implementation - Soberon, Jorge; Cavner, Jeff (Biodiversity Informatics, 2015)
In this work we present mathematical notation and formulae relating a number of indices of the biodiversity pattern of an aggregate of species, and an Open Source implementation of them as a plug-in for the increasingly popular Open Source geographical information system Quantum GIS. We provide detailed formulae relating three indices of beta diversity, two of pattern of nestedness, one of checkerboard pattern, and two of ratios of variances. The above is done by deriving six vectors from the full presence-absence matrix. Our GIS implementation is done via Web Services, tapping the LifeMapper platform for calculating potential species distributions.